Relative Importance of Perceived Value, Satisfaction and Perceived Risk on Willingness to Pay More - Banu Külter Demirgüneş (International Review of Management and Marketing, 2015)
The consumer perceived value construct is a very important component in the consumer value literature and it has been identified as one of the most important measures for gaining a competitive advantage. All its consequences can be combined in a construct, defined as consumer behavior. The present article sustains the idea that consumer’s perceived value can been associated with satisfaction, which leads a behavioral intention such as willingness to pay a higher price. In the case of potentially undesirable and risky conditions, perceived risk can also be determinant of consumer behavior. Regarding the value and risk perceptions of consumers on a specific sector, this paper contributes to define these perceptions’ influences on a mobile phone industry. Accordingly, this study posits a path model of satisfaction, perceived value, risk and willingness to pay a higher price. The results suggest a link of perceived value dimensions and satisfaction with the product, also the hypothesized assumptions of the link of satisfaction and willingness to pay a higher price were supported by the results. The results also reveal negative influence of perceived risk on behavioral intention.